2008
DOI: 10.1084/jem.20071364
|View full text |Cite
|
Sign up to set email alerts
|

TL1A–DR3 interaction regulates Th17 cell function and Th17-mediated autoimmune disease

Abstract: T helper type 17 (Th17) cells play an important pathogenic function in autoimmune diseases; their regulation, however, is not well understood. We show that the expression of a tumor necrosis factor receptor family member, death receptor 3 (DR3; also known as TNFRSF25), is selectively elevated in Th17 cells, and that TL1A, its cognate ligand, can promote the proliferation of effector Th17 cells. To further investigate the role of the TL1A–DR3 pathway in Th17 regulation, we generated a TL1A-deficient mouse and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
218
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(246 citation statements)
references
References 43 publications
17
218
1
10
Order By: Relevance
“…As such, our data provide an insight into the formation of these highly pathogenic cells in vivo, and suggest that targeting of inflammatory monocytes could lead not only to a decrease in the production of proinflammatory cytokines, but also in a reduction in Th17 cells. Recent literature indicates that, in addition to multiple cytokine signals, cell-derived factors may be required for the generation or expansion of Th17 cells (2,27,28). We show that in vitro activated monocytes from both HC and RA patients induce Th17 responses in an IL-1␤/TNF-␣-dependent fashion.…”
Section: Discussionmentioning
confidence: 75%
“…As such, our data provide an insight into the formation of these highly pathogenic cells in vivo, and suggest that targeting of inflammatory monocytes could lead not only to a decrease in the production of proinflammatory cytokines, but also in a reduction in Th17 cells. Recent literature indicates that, in addition to multiple cytokine signals, cell-derived factors may be required for the generation or expansion of Th17 cells (2,27,28). We show that in vitro activated monocytes from both HC and RA patients induce Th17 responses in an IL-1␤/TNF-␣-dependent fashion.…”
Section: Discussionmentioning
confidence: 75%
“…In vitro, CD4 1 T cells that cannot signal via DR3 are defective in the secretion of a number of cytokines including IL-2, IL-4, IL-5, IL-13, IL-10, IL-17, but not IFN-g [5,14]. Furthermore, addition of TL1A enhanced the proliferation of in vitro generated Th17 cells upon re-stimulation, but had no effect on the proliferation of Th1 cells [13]. Consistent with these findings transgenic mice that constitutively express TL1A have increased levels of IL-13 and IL-17 but not IFN-g under steady-state conditions [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using TL1A À/À or DR3 À/À mice have revealed a role for TL1A/DR3 in exacerbating Th2-and Th17-cell-dependent inflammatory and autoimmune conditions [5,13]. In contrast, no studies have reported a role for DR3 in host immune responses to infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DR3 экспрессируется преимущественно в се-лезенке, тимусе и лейкоцитах периферической крови (T-и В-лимфоцитах, NK-и NKT-клетках, макрофагах) [8]. Описана важная роль данного рецептора как в регуляции иммунных реакций, так и в развитии воспалительных, аутоиммунных, онкологических и инфекционных заболеваний [5,7,9,10].…”
Section: Introductionunclassified